1990
DOI: 10.1116/1.576378
|View full text |Cite
|
Sign up to set email alerts
|

I ns i t u scanning tunneling microscopy of platinum (111) surface with the observation of monatomic steps

Abstract: I n situ scanning tunneling microscopy was applied to single-crystal platinum (111) surfaces both before and after electrochemical potential cycling in an aqueous sulfuric acid solution. Steps observed on a Pt(111) facet were usually located on nearly parallel straight lines or on the directions forming an angle of close to 60°, as expected for a surface with threefold symmetry. The height of each step was in accord with the monatomic step height of 0.238 nm on the Pt(111) surface. Randomly oriented islands a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(132 citation statements)
references
References 0 publications
9
123
0
Order By: Relevance
“…The voltammetric profile of the electrode in 0.5 M H 2 SO 4 is always recorded to assure that the surface is well prepared and clean. The upper potential limit is always chosen so that oxide formation is avoided, to prevent surface disordering [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…The voltammetric profile of the electrode in 0.5 M H 2 SO 4 is always recorded to assure that the surface is well prepared and clean. The upper potential limit is always chosen so that oxide formation is avoided, to prevent surface disordering [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…[137][138][139][140] Itaya and co-workers showed that after a few cycles between 0.05 V and 1.5 V, an initially ordered Pt terrace becomes corrugated, covered with monoatomic or diatomic pits and islands. 137,138 According to Wakisaka et al, the first step in this roughening process occurs at anodic potentials, at high coverages of O*, where the Pt(111) surface starts to mildly buckle, and subsurface oxides form. 139 Even so, the surface remains largely intact until the reduction sweep, where at 0.5 V, the terraces becomes abruptly more corrugated.…”
mentioning
confidence: 99%
“…39,40 In 1990, we used in-situ STM to provide direct evidence of the existence of a well-defined surface in solution. 41 Figure 2(b) shows the first STM image of a flame-annealed Pt(111) surface in a sulfuric acid solution. The height of each step was approximately 0.23 nm, in accord with the monatomic step height of 0.238 nm on the Pt(111) surface.…”
Section: Preparation Of Well-defined Electrode Surfacesmentioning
confidence: 99%